2020
DOI: 10.1111/1440-1681.13375
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: Important participants and potential therapeutic targets for myocardial ischaemia reperfusion injury

Abstract: Myocardial ischaemia reperfusion (I/R) injury is one of the leading causes of coronary artery disease-associated morbidity and mortality. While different strategies have been used to limit I/R injuries, cardiac functions often do not recover to the normal level as anticipated. Recent studies have pointed to important roles of long noncoding RNAs (lncRNAs) in the development of myocardial I/R injury. LncRNA is a class of RNA molecules of more than 200 nucleotides in length which are not translated into proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In comparison to the conventional diagnosed approach, circulating lncRNAs are noninvasive and innocuous, with highly sensitive and accurate advantages [30]. Furthermore, lncRNAs may participate in the progression of CAD via mediating apoptosis and autophagy, two forms of programmed cell deaths [15]. On account of these strengths, this study explored circulating lncRNAs related to apoptosis and autophagy for CAD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to the conventional diagnosed approach, circulating lncRNAs are noninvasive and innocuous, with highly sensitive and accurate advantages [30]. Furthermore, lncRNAs may participate in the progression of CAD via mediating apoptosis and autophagy, two forms of programmed cell deaths [15]. On account of these strengths, this study explored circulating lncRNAs related to apoptosis and autophagy for CAD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both serum levels in CAD patients are higher than healthy controls [14]. lncRNAs with >200 nucleotides may participate in the pathophysiological processes of CAD including autophagy and apoptosis [15]. On account of their tissue and cell specificity, circulating lncRNAs are promising diagnostic markers for various diseases [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro RNAs (miRNAs) and long non-coding RNAs (lncRNAs) are two important families of ncRNAs with lengths of ~21-24 nucleotides and exceeding 200 nucleotides, respectively [10]. In myocardial I/R injury, many studies have shown that both miRNAs and lncRNAs are largely involved [11,12]. For instance, lncRNA SNHG8 (small nucleolar RNA host gene 8) mediates myocardial muscle cell necrosis following I/R [13].…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA TRINGS interacts with STRAP and thwarts STRAP-GSK3 β -NF- κ B necrotic pathways [ 33 ]. Moreover, other studies have found that myocardial ischemia-reperfusion injury can lead to abnormal expression of lncRNAs in cardiomyocytes, thus affecting various cellular functions such as mitochondrial homeostasis, apoptosis, necrosis, and autophagy [ 34 ]. However, functions adopted by necroptosis-associated lncRNAs for treating or prognostic determination of KIRC are still unclear.…”
Section: Introductionmentioning
confidence: 99%